2021
DOI: 10.1080/14756366.2021.2015342
|View full text |Cite|
|
Sign up to set email alerts
|

1,3,4-Oxadiazole-naphthalene hybrids as potential VEGFR-2 inhibitors: design, synthesis, antiproliferative activity, apoptotic effect, and in silico studies

Abstract: In the current work, some 1,3,4-oxadiazole-naphthalene hybrids were designed and synthesised as VEGFR-2 inhibitors. The synthesised compounds were evaluated in vitro for their antiproliferative activity against two human cancer cell lines namely, HepG-2 and MCF-7. Compounds that exhibited promising cytotoxicity ( 5 , 8 , 15 , 16 , 17 , and 18 ) were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 79 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…During apoptosis, phosphatidylserine translocates to the outer plasma membrane; then Annexin V can especially detect it. Live and dead cells are identified by 7‐AAD, a DNA specific dye [18] . As shown in Figure 1, analysis of the apoptotic effect of the compound A 5 in Q1 shows necrotic cells; in Q2, cells undergoing progressive apoptosis and secondary necrosis; in Q3, cells undergoing primary apoptosis; in Q4, live cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During apoptosis, phosphatidylserine translocates to the outer plasma membrane; then Annexin V can especially detect it. Live and dead cells are identified by 7‐AAD, a DNA specific dye [18] . As shown in Figure 1, analysis of the apoptotic effect of the compound A 5 in Q1 shows necrotic cells; in Q2, cells undergoing progressive apoptosis and secondary necrosis; in Q3, cells undergoing primary apoptosis; in Q4, live cells.…”
Section: Resultsmentioning
confidence: 99%
“…Live and dead cells are identified by 7-AAD, a DNA specific dye. [18] As shown in Figure 1, analysis of the apoptotic effect of the compound A 5 in Q1 shows necrotic cells; in Q2, cells undergoing progressive apoptosis and secondary necrosis; in Q3, cells undergoing primary apoptosis; in Q4, live cells. Accordingly, after 24 hours of treatment with A 5 , our results showed that the percentages of apoptotic cells (Q2 + Q3) for 25 μM was 4.30 %; and for 50 μM, 5.67 %.…”
Section: Apoptotic Effect Of a 5 On Mcf-7 Cell Linementioning
confidence: 96%
“…These results were found to be identical to the reported data. 36 The docking score for compound 9d was −8.85 kcal mol −1 . Through its pharmacophoric group, it formed two hydrogen bonds with Glu883 and Asp1044.…”
Section: Effect On Cell Cycle Progressionmentioning
confidence: 99%
“…A good antiproliferative effect was observed for Compound ( 142 ) against both cell lines and inhibitory activity was demonstrated against VEGFR-2. It also induced 22.86% apoptosis compared to 0.51% apoptosis in control (HepG2) cells [ 129 ].…”
Section: Miscellaneous Anticancer Properties Of 134-oxadiazole Deriva...mentioning
confidence: 99%